Sand transport in multiphase pipelines - Yan, Wei (Cranfield University, 2010)
Over the life of an oil and gas reservoir, it is likely to encounter sand production. In offshore production fields, as there are lack of processing facilities nearby, gas, liquid and sand are often transported together in long distance pipelines. The existence of sand could accumulate in the pipelines under inappropriate operation condition and eventually will lead to a blockage. Thus, to design such systems requires knowledge on how sand is transported, when and where it will accumulate. This thesis summarizes the experimental work undertaken using the 2 inch, 3 inch and 4 inch multiphase facilities. Generally, the main objectives of the experiments were to i) observe and enhance the understanding of sand transport characteristics in water and air-water flows; ii) investigate sand concentration effect and pipe diameter effect on sand minimum transport condition (MTC); iii) investigate the effect of pipeline orientation (0, +5, +10 and +20 degrees) and viscosity effect (Carboxy Methyl Cellulose (CMC) solution with viscosity of 7, 20cP; Oil with viscosity of 105, 250 and 340cP) on sand MTC; iv) validate the equivalent pressure drop concept for predicting sand MTC in sand-air-water flow and v) extend current MTC prediction model for sand-water flow to account for different sand concentrations . Similar sand behaviour was observed in horizontal sand-water flow in all pipe sizes tested. At minimum transport velocity, sand particles were observed transporting in form of sand streaks. For horizontal sand-air-water flow, sand transport characteristics and MTC were strongly dependent on the air-water flow regime. Sand was found to be transported more efficiently within slug or roll wave body, where turbulence is generated intensively. Parametric studies were conducted to investigate the factors affecting sand MTC in water and air-water flows in pipeline. It was found that the MTC will increase as sand concentration and pipe diameter increase. Pipeline orientation was found having little effect on sand behaviours and MTC in upwardly inclined water flow. However, in upwardly inclined air-water flow, although sand particles were observed sometime moving backward with the liquid film, the superficial gas and liquid velocities required to transport sand were less than those in the horizontal pipeline due to the fact that slug flow regime was found more prevailing in inclined pipeline. In addition, the liquid viscosity effect on sand MTC in single phase liquid flow was investigated due to the increase of concerns relating to solids transport in high viscosity crudes. It appeared that, in turbulent flow, sand MTC increased slightly as the fluid viscosity increased. However, when the bulk flow became laminar, the MTC decreased as the fluid viscosity increased. After visually obtained the sand MTC in air-water flow, the measured pressure gradients were compared between MTC condition for sand-water flow for different sand concentrations, the results indicate that the equivalent pressure gradients concept is a valid approach to extend the sand MTC prediction from water flow to air-water flow conditions for the purpose of pipeline design. Two concentration correction correlations (dual range and single range) were proposed. The modified model could account for a wider range of sand concentration (from 0.000005 to 0.3 volume fraction) in water flow. The predicted MTC velocities showed good agreement with the experimental results.